(untitled) (Journal of Atomic and Molecular Sciences, 2021)
Based on the Lamé equation and Jacobi elliptic function, the perturbation method is applied to some nonlinear evolution equations. And there many multi-order solutions are derived to these nonlinear evolution equations. These multi-order solutions correspond to the different periodic solutions, which can degenerate to the different soliton solutions. The method can be also applied to many other nonlinear evolution equations.